Identification of Differentially Expressed Proteins and Development of Molecular Markers for the Identification of Metroxylon sagu in the Regions of Sarawak - Mehvish, Nisar (Universiti Malaysia Sarawak (UNIMAS), 2021)
Sago palm (Metroxylon sagu) is important and considered as an asset crop in Sarawak, Malaysia. Sago palm grows well in the rough, swampy peat, from low flooded areas to uplands and acidic to neutral soils. It is the most productive and promising in producing starch can store a significant amount of carbohydrate in the trunk. The study of sago palm here aimed to develop molecular markers and proteins for the identification of Metroxylon sagu. Amplified fragment length polymorphism was employed to determine the genetic variations of sago palm between fifteen populations collected from three different locations: Mukah, Pusa and Samarahan. Based on 35,016 polymorphic fragments generated from thirty-two primer combinations, polymorphic information content (PIC), marker index (MI) and resolving power (RP) averaged 0.269, 0.005157 and 51.52039 per primer combination, respectively, were obtained, signifying the effectiveness and accuracy of the AFLP marker. Mukah showed higher diversity (I = 0.428, H = 0.232) while Pusa showed the lowest (I = 0.367, H = 0.240). The average value of the Shannon information index was 0.404. AMOVA showed 99% of the variation was found within the population. The principal coordinate analysis (PCoA) explained 66.36% of variation on three components. This study explained that AFLP markers could be considered as an effective and reliable method to assess the genetic variation and in the identification of the M. sagu. In this study, proteomics approach was also utilised to check the protein expression in different populations of M. sagu. PEG fractionation extraction method was used to extract the proteins from leaf tissue, and proteins were separated by two-dimensional gel electrophoresis (2-DE). Differentially expressed protein spots were subjected to mass spectrometry. The Mass spectrometric analysis identified 26 differentially expressed proteins, representing different enzymes and proteins which showed significantly different regulation in all fifteen-population. The expression profile of the proteins identified showed that the M. sagu in Mukah region showed upregulation in genes as compared to Pusa and Samarahan. The M. sagu from Pusa showed down regulation. The identified proteins mainly function in growth and development, metabolic pathways, glycolysis, carbon utilization, and biotic and abiotic stress. This study signifies that the proteins identified through differentially expressed proteome provided support for the identification of the M. sagu. The results obtained from the protein expression profile somehow corelate with the results obtained from genetic studies. M. sagu in Mukah region showed high genetic variation and Pusa showed lowest. In the same way the expression profile of the proteins identified showed that the M. sagu in Mukah region showed up-regulation in genes which are associated with growth, development and reproduction and exhibit marked resistance to different abiotic and biotic stress. The genomic and AFLP fragment studies are the most significant technologies to investigate the extremely complex and dynamic biological system, as the technologies provide a detailed and precise analysis of cellular state during growth, development, and other environmental factors.